Effects of six months of aerobic and resistance training on metabolic markers and bone mineral density in older men on androgen deprivation therapy for prostate cancer. Issue 7 (September 2020) - Papadopoulos, Efthymios; Mina, Daniel Santa; Culos-Reed, Nicole; Durbano, Sara; Ritvo, Paul; Sabiston, Catherine M.; Krahn, Murray; Tomlinson, George; O'Neill, Meagan; Iqbal, Amna; Timilshina, Narhari; Matthew, Andrew; et al.
Abstract: Background: Androgen deprivation therapy (ADT) for prostate cancer (PCa) is associated with metabolic perturbations and declines in bone mineral density (BMD). Exercise interventions provide multiple health benefits to older men on ADT; however, their effect on metabolic biomarkers and BMD remains unclear. Methods: A secondary analysis of a phase II randomized controlled trial was conducted to assess the effect of a six-month moderate-intensity aerobic and resistance exercise program on metabolic biomarkers and BMD in men on ADT. Participants were randomized to three different exercise delivery models: personal training; supervised group exercise; or home-based exercise. Analysis of metabolic biomarkers (lipid profile and glucose) was conducted at baseline, six and twelve months. BMD of the lumbar spine, femoral neck and hip were assessed at baseline and twelve months. Both within- and between-group analyses of change scores adjusted for baseline values were performed. Results: Forty-eight men (mean age 69.8y) were enrolled. Baseline values of metabolic biomarkers and BMD were comparable between groups and the three groups were combined for the primary analysis. At six months, no changes in metabolic biomarkers were found; however, at twelve months low-density lipoprotein (+0.28 mmol/L; 95%CI, 0.04 to 0.51) and total cholesterol (+0.31 mmol/L; 95%CI, 0.00 to 0.61) were significantly increased from baseline. No changes were found in BMD. In a secondary between-group analysis, no improvements were observed for any metabolic biomarker or BMD measurement. Conclusions: Different exercise prescription parameters (modality and intensity) or combined diet/exercise interventions may be needed to foster favorable metabolic and skeletal adaptations during ADT.